2015
DOI: 10.1002/dys.1504
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Driving Performance as Evidence of a Magnocellular Deficit in Dyslexia and Visual Stress

Abstract: High comorbidity and an overlap in symptomology have been demonstrated between dyslexia and visual stress. Several researchers have hypothesized an underlying or causal influence that may account for this relationship. The magnocellular theory of dyslexia proposes that a deficit in visuo-temporal processing can explain symptomology for both disorders. If the magnocellular theory holds true, individuals who experience symptomology for these disorders should show impairment on a visuo-temporal task, such as driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Fisher, Chekaluk, and Irwin (2015) found that the scores in a self-report measure of dyslexia for adults (the Adult Checklist; Smythe & Everatt, 2001) were positively associated with the number of errors in response to road signs in a driving simulator, and Taylor, Chekaluk, and Irwin (2016) reported that the score in the same checklist was negatively associated with the score on a test assessing road sign comprehension as well as with the scores on some tests measuring situation awareness for road sign information. The authors of these works posited that individuals with dyslexia have trouble with traffic sign processing because they suffer from a general reduced ability to temporally order sensory information, in agreement with the temporal hypothesis of dyslexia (Gori, Cecchini, Bigoni, Molteni, & Facoetti, 2014).…”
Section: Previous Research On the Effects Of Dyslexia On The Processimentioning
confidence: 99%
“…Fisher, Chekaluk, and Irwin (2015) found that the scores in a self-report measure of dyslexia for adults (the Adult Checklist; Smythe & Everatt, 2001) were positively associated with the number of errors in response to road signs in a driving simulator, and Taylor, Chekaluk, and Irwin (2016) reported that the score in the same checklist was negatively associated with the score on a test assessing road sign comprehension as well as with the scores on some tests measuring situation awareness for road sign information. The authors of these works posited that individuals with dyslexia have trouble with traffic sign processing because they suffer from a general reduced ability to temporally order sensory information, in agreement with the temporal hypothesis of dyslexia (Gori, Cecchini, Bigoni, Molteni, & Facoetti, 2014).…”
Section: Previous Research On the Effects Of Dyslexia On The Processimentioning
confidence: 99%